Digitalisasi Pendidikan Agama Islam: Peran Software dalam Proses Pembelajaran - Nur, Zulfikah; Yaumi, Muhammad; Arsyad, Azhar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the benefits and challenges of software implementation. This study uses a literature study method to explore the role of software in the digitization of Islamic education. The sources were selected based on their relevance to key themes, including the integration of technology in Islamic education, the use of digital tools in the pedagogical process, and the challenges and opportunities associated with educational software. Data collection follows a structured process, which involves searching for keywords in databases such as Google Scholar with terms such as